IMMIGRATION POLYTECHNIC ADMINISTRATOR ASSISTANCE FOR MIDDLE OR PRIVATE SCHOOL STUDENTS IN SEMARANG CITY - Anita Herlina (Jurnal Abdimas Imigrasi, 2020)
Continuing education is the right for every student. In this case, high school or equivalent students have the right to proceed to a higher level. Colleges become solutions. However, every prospective student must precisely determine the steps and precisely prepare them. The Indonesian Student Communications Forum (FMKI) conducts mentoring or socialization for prospective learners to determine their future through an alternative college of high School. The Immigration Polytechnic also has a sense of responsibility for the next generation of Indonesian immigration officer. Therefore, this mentoring has a positive impact in two directions, prospective learners and the Immigration Polytechnic